Understanding the Online Conspicuous Purchase Pattern of Indian Millennial with respect to Fashion Clothing Brands - Saraswat, Shikha; Bisht, Swati; Prakash, Namrata (International Journal of Psychosocial Rehabilitation, 2020)
–I got a closet full of clothes but I got nothing to wearI wanna shop‘Song ‘Me and Mirror by Jordan Sparks’The above lyrics of the song depict the situation prevalent amongst most of the college-going youth in the country today. The youth in the country always aspire to have more- more of every pleasure and possession in life and tech- gazettes and fashion clothes top their list. This paper focuses on understanding the motivation of the youth while shopping for fashion apparel brands.The millennial generation is more informed of the choices available for making a purchase. There is a high level of consciousness among them on ‘What to wear, when and why’. The irony of the youth of today is that what you wear decides on who you are and one will look good only when one wears ‘good’ so the focus shifts towards what to wear. This primarily is because of the World Wide Web that makes any and every information available by a click. But what is it that motivates the youth towards making a purchase or simply towards strengthening the purchase intention needs to be understood deep. It could possibly be a set of reasons put together. Peer influence, the brand, promotional offers, price, fashion trend all put together or even individually or in some combinations. The word ‘Need’ has long been replaced by ‘desires’ especially when it comes to the present generation of college going students. It will not be wrong to say that for the fashion industry change is the only constant as what is fashion today may become obsolete tomorrow. Fashion is very dear to the millennial because fashion reflects the image of self in the eyes of others which is important to them.The millennials spend a lot of time on the internet and, therefore, amongst the urban millennial online shopping tendencies have enhanced. Companies therefore should work on designing their virtual shopping space in such a way that it motivates the visitor to stay for longer on the website and this could lead to a higher probability of shopping from that site. A less attractive site may not be able to hold the attention and time of the visitor for long.The paper aims to identify the factors that influence the purchase intention of the millennial towards fashion products and to understand the impact of e-reviews on purchase decisions.